2016
DOI: 10.1016/j.fuel.2016.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected inhibition of CO2 gas hydrate formation in dilute TBAB solutions and the critical role of interfacial water structure

Abstract: Gas hydrates formed under moderated conditions open up novel approaches to tackling issues related to energy supply, gas separation, and CO 2 sequestration. Several additives such as tetra-n-butylammonium bromide (TBAB) have been empirically developed and used to promote gas hydrate formation. Here we report unexpected experimental results which show that TBAB inhibits CO 2 gas hydrate formation when used at minuscule concentration. We also used spectroscopic techniques and molecular dynamics simulation to gai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 48 publications
(67 reference statements)
3
46
0
Order By: Relevance
“…However, the literature suggests that the advantage of using TBAB lies in its ability to be a thermodynamic promoter, which is not yet noticeable at these low concentrations. Nguyen et al also reported a decreasing trend with increasing TBAB concentration, similar to the one presented here, but in carbon dioxide gas hydrate systems. They indicated that gas uptake is at a minimum at 1250 ppm TBAB, and gas uptake will increase with either increasing or decreasing the TBAB concentration from this point.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…However, the literature suggests that the advantage of using TBAB lies in its ability to be a thermodynamic promoter, which is not yet noticeable at these low concentrations. Nguyen et al also reported a decreasing trend with increasing TBAB concentration, similar to the one presented here, but in carbon dioxide gas hydrate systems. They indicated that gas uptake is at a minimum at 1250 ppm TBAB, and gas uptake will increase with either increasing or decreasing the TBAB concentration from this point.…”
Section: Resultssupporting
confidence: 88%
“…This means that the driving force for this concentration is approximately 5 % lower than the other concentrations (1423 kPa versus 1500 kPa). Nguyen et al have explained this inhibition at dilute TBAB concentration as a gas‐water interface adsorption of TBAB that gives rise to inhibition at low concentrations. The promotion effect of TBAB is not strong enough at these low concentrations to compensate for the inhibition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, while SDS is widely known an effective promoter, Sowa et al 36 recently reported that this surfactant could act as an inhibitor of gas hydrate formation in a wide range of experimental condition. Similarly, we have shown in our recent work 37 that tetra-n-butyl ammonium bromide (TBAB), also a well-known gas hydrate promoter, could display a strong inhibiting effect on CO 2 gas hydrate formation when it was used at millimolar concentration.…”
mentioning
confidence: 55%
“…In this section, we show how the effect of a mixture of SDS and TBAB is different from the individual effect of each surfactant. In our recent work 37 , we showed that TBAB (tetra-nbutylammonium bromide) displayed a strong inhibition of carbon dioxide hydrate formation when it was used at the concentration of 3.6 mM. Thus, we used this concentration for our aim here.…”
Section: Effect Of Mixture Of Sds and Tbabmentioning
confidence: 99%